PENGEMBANGAN LEARNING CONTENT MANAGEMENT SYSTEM YANG MENDUKUNG PENINGKATAN EFEKTIFITAS PROSES BELAJAR JARAK JAUH - Surendro, Kridanto (Jurnal Teknik Elektro, 2005)
Learning Content Management System is a system that is used to create, store, assemble, and deliver personalized elearning content in the form of learning objects. The system gives advantages for the student because the course contents are customized as needed by the students. LCMS gives authors, instructor, and subject matter experts with the mean to create e-learning content more efficient and used it to track the learner progress and performance across all types of learning activities. This paper discuss the development of LCMS application system. Abstract in Bahasa Indonesia : Learning Content Management System (LCMS) merupakan suatu sistem yang digunakan untuk mengelola materi pembelajaran secara personal dalam e-learning. Sistem ini memberikan manfaat bagi siswa karena materi belajar diberikan sesuai dengan kemampuan dan kebutuhan siswa. Bagi pengajar sistem ini dapat digunakan untuk membuat materi pembelajaran secara efisien dan dapat digunakan untuk melihat perkembangan dan kemampuan siswa dalam belajar. Dalam makalah ini akan dikemukakan tentang upaya pengembangan perangkat lunak LCMS. Katakunci: Learning Content Management System, eLearning, Computer Adaptive Test